Prediction of current harmonics in induction motors with artificial neural network - (:unkn) unknown (IEEE Computer Society, 2007)
In this paper, Artificial Neural Network (ANN) technique has been used for the estimation of voltage THD (Total Harmonic Distortion), and current THD, mainly from input and output measurements of five different chorded induction motors fed from a pulse width modulation inverter voltage supply. A sinusoidal pulse-width modulation (SPWM) inverter feeding five different chorded three-phase induction motors were tested up to first thirty harmonic voltage component at different loads. The results show that the artificial neural network model produces reliable estimates of voltage THD and current THD. © 2007 IEEE.